Pengaruh Penerapan Pola Pembelajaran Flipped Classroom Terhadap Kemandirian dan Hasil Belajar Biologi - Thalib, Munawwarah; Ismail, Ismail; Wiharto, Muhammad (Universitas PGRI Semarang, 2022)
This study aims to: (1) Find out the biology learning outcomes of class VIII MTsN Takalar students through flipped classroom learning patterns. (2) Knowing the independence of learning biology for students of class VIII MTsN Takalar through flipped classroom learning patterns. (3) Knowing the influence of the application of flipped classroom learning patterns on the learning outcomes of students of class VIII MTsN Takalar. (4) Knowing the influence of the application of flipped classroom learning patterns on the learning independence of class VII I MTsN Takalar students. This research is Quasi experimental. The population in this study was all students of class VIII, for the 2022/2023 school year at MTsN Takalar, totaling 103 students divided into four study groups, then sampling was carried out randomly and two study groups were selected, namely class VIII C with 27 people and class VIII B with 26 people. The results showed that: (1) The learning independence of students of class VIII MTsN Takalar through flipped classroom learning patterns is in the high category and the learning independence of students taught through conventional learning isin the sufficient category. (2) The learning outcomes of students of class VIII MTsN Takalar through the flipped classroom learning pattern are in the very high category and the learning outcomes of students who are taught using conventiononal berada learning in the high category. (3) There is an influence on the application of flipped classroom learning patterns on the independence and learning outcomes of class VIII MTsN Takalar students.